Developing predictive models for computing the mechanical behaviour of soil structure interaction problems involving sandy materials - Bark, Hussein Ali (My University, 2027)
Integrate a FEA software with a new soil material model and use it to generate a dataset of Soil Structure Interaction results to train Artificial Intelligence algorithms.
Keywords: Soil Structure Interaction; Artificial Intelligence; Earthquake engineering; Programming; Finite Element Method; Material Constitutive Models